Atomic layer deposition and structure optimization of ultrathin Nb2O5 films on carbon nanotubes for high-rate and long-life lithium ion storage. (20th January 2020) - Zhu, Shengyun; Xu, Penghui; Liu, Junqing; Sun, Jiaming
Abstract: Niobium pentoxides (Nb2 O5 ) as anode materials has attracted tremendous research interest due to its great potential in rate capability and cyclic durability. Nevertheless, the low electrical conductivity and weak structural controllability of Nb2 O5 hinders its practical application. Herein, amorphous Nb2 O5 thin films are conformally deposited on carbon nanotubes (CNTs) by controlled atomic layer deposition (ALD) and three types of crystalline Nb2 O5 @CNTs composites are obtained by post-deposition annealing. Moreover, the effects of deposition temperature and annealing temperature on the crystal structure and surface morphology of Nb2 O5 @CNTs are investigated. Based on these, the electrochemical performances of Nb2 O5 @CNTs composites as anode materials are compared in lithium half cells. Impressively, ultrathin and uniform Nb2 O5 nanocrystal film with hexagonal ( TT ) phase on CNTs delivers a capacity of 325.1 mAh g −1 at 0.2 A g −1 . Even at a high current density of 3 A g −1, a stable capacity of 170 mAh g −1 is still achieved over 4000 cycles. Its high-rate and long-life lithium ion storage is mainly attributed to the synergistic effects of carbon nanotubes, TT -phase Nb2 O5, and ultrathin film structure. Therefore, this synthetic strategy facilitates the development of Nb2 O5 as anode materials for high-rate and long-life lithium/sodium ion batteries.